DETERMINAN PENYERAPAN TENAGA KERJA DI KAWASAN TIMUR INDONESIA TAHUN 2019-2024 - Putra Tarigan Silangit, Reviando; Budi Setiawan, Avi (Penerbit Lafadz Jaya, 2025)
This study analyzes the determinants of labor absorption in Eastern Indonesia (KTI) during the 2019-2024 period using a quantitative approach with panel data regression method. The results of the model specification test indicate that the Random Effect Model (REM) is the best model applied in this study. Overall, the independent variables, including Gross Regional Domestic Product (GRDP), Provincial Minimum Wage (UMP), Investment, and Average Length of Schooling, simultaneously have a significant influence on labor absorption in KTI. Partially, GRDP (X1) is proven to have a positive and significant effect on labor absorption, indicating that increased economic activity and production drive the demand for labor. The Provincial Minimum Wage (UMP) (X2) shows a negative and significant effect on labor absorption, which can be explained by the increase in operational costs for companies, especially in labor-intensive sectors. Investment (X3) has a positive and significant effect on labor absorption, affirming its vital role in creating employment through increased production capacity and innovation. Lastly, Average Length of Schooling (X4) also significantly contributes positively to labor absorption, highlighting the importance of improving human resource quality through education to produce a more competitive workforce. The contribution of all independent variables in explaining the variation in labor absorption is 78.04%. This research emphasizes the importance of monitoring variables such as GRDP, UMP, Investment, and Average Length of Schooling in relation to labor absorption in Eastern Indonesia.